Sustainable Agricultural Tehcnologies on Rice Farming: Case of Subaks’ in Bali Province, Indonesia - Wichaya Komin; Gede Sedana (Dwijendra University, 2019)
Rice farming is very important to provide food for the population in the country. The increased rice productivity in Indonesia has been done since 1968 through the green revolution program. However, this program has brought the negative impacts for the physical environment which contributes to decreased productivity. Therefore, the effort to sustain the agricultural development should be taken by the government by applying sustainable agricultural technologies. The purpose of this study is to describe the implementation sustainable agricultural technologies, particularly on rice farming in Bali Province, Indonesia. The results of study pointed out that the sustainable agricultural technologies in rice farming could be done by implementing SRI, organic farming, and integrated pest management. These have an important role to ensure the increased productivity of rice. Besides, these could also support the economic activities in the upstream to the downstream sectors. It is recommended to government and other stakeholders to consider ecological and environmental aspects in the application of new agricultural technologies.